Contribution of the bitter taste signaling pathway to lung inflammation during Staphylococcus aureus-induced pneumonia - Liu, Ling-Ling; Li, Feng; Zhu, Meng-Min; Niu, Bo-Wen; Huang, Yu; Chen, Lixiang; Yang, Hua; Qin, Boyin; Zhou, Xiaohui (Frontiers in Immunology, 2025)
Bitter taste receptors (TAS2Rs), initially identified for chemosensory roles in the tongue, are expressed in extraoral tissues, including the airways. However, to date, it remains unclear whether bitter signaling is associated with susceptibility to bacterial infection in the lower airways and whether bitter signaling actually participates in the immune response in lung infection has yet to be genetically established. Here, we investigated the role of TAS2R signaling in Staphylococcus aureus-induced murine pneumonia via wild-type (WT) and several mutants (mTas2r104-/-/105-/-, mTas2r105-/-/114-/-, mTas2r104-/-/105-/-/114-/-, Gnat3-/- and Gnat3-/–mTas2r104-/-/105-/-) mice. Genetic disruption of TAS2Rs altered compensatory expression of other bitter receptors in the trachea and lungs, but did not affect immune cell composition in the lungs or thymus. Bitter receptor-deficient mice exhibited exacerbated pulmonary lesions at day 3 (D3) post-infection. Pulmonary infection significantly upregulated mTas2r105,106, 107, 108, 126, 136, 138 and Gnat3 in the lung. TAS2R signaling deficiency downregulated the expression of cytokines (e.g., IL-10, MIP-2) and antimicrobial peptides in the lungs and trachea, increased CD68+ macrophages in D3 lung tissues, amplified Ki67+ cell proliferation in alveolar and bronchiolar regions, and even impaired recovery from lung injury by day 14 (D14). Mechanistically, bitter taste pathway disruption dysregulated the mTOR pathway, reduced eNOS expression, and delayed resolution of pneumonia-induced injury. In summary, the current results collectively indicate that bitter taste signaling can modulate innate immune and inflammatory responses during S. aureus-induced lung infection.